The dialectic of fiqh understanding and the female Imam-Khatib tradition in Balingka, West Sumatra, Indonesia - ikhwan ikhwan; Azhariah Fatia; Junizar Suratman; Muhammad Nabil Ramadhan; Alfaiz Alfaiz (Indonesian Journal of Islam and Muslim Societies, 2022)
This study aimed to determine the relationship between the fiqh understanding and women’s religious role in the tradition of female priests and preachers (imam-khatib) in Balingka, West Sumatra, Indonesia. A qualitative approach was used with data obtained through interviews with informants, including female priests (imam), religious scholars, village guardians, community leaders, and women figures in Balingka. Furthermore, documentation and observation were also used to collect data. The results showed a relationship between the dynamics of  fiqh understanding and women’s religious role. A moderate fiqh understanding makes the practice of female imam-khatib persist, supporting its recognition, and acceptance. Conversely, radical fiqh thoughts make the tradition of female imam-khatib criticized and challenged. The shift in fiqh understanding brings this tradition to an end after lasting for almost a century in Balingka. The study of Islam socialized by the Salafis through television and internet media shifted the understanding of fiqh from a moderate to a radical style, bringing this tradition to an end. Consequently, women are marginalized from their religious roles and are subordinate to men’s roles.